Mechano‐fenton–piranha oxidation of carbon nanotubes for energy application - Wei, Chaohui; Akinwolemiwa, Bamidele; Wang, Qingfu; Guan, Li; Xia, Lan; Hu, Di; Tang, Bencan; Yu, Linpo; Chen, George Z. (Wiley-VCH Verlag, 2019)
Emission of nitrogen oxides (NOx) from chemical processing of materials is a serious environmental concern, frustrating the development of many innovative technologies. For example, sulfonitric oxidation is the most widely used method for processing carbon nanotubes (CNTs), producing a large amount of NOx. As a result, large scale applications of CNTs for downstream purposes remain challenging. Herein, a NOx-free oxidation method is proposed for CNTs processing. It starts with mechanically grinding, and then oxidizing the CNTs by hydroxyl radicals in sealed reactors. Such processed CNTs are shorter, possess balanced surface oxygen containing groups without compromising the original CNT integrity, and can disperse readily in water. These are desirable for making various CNT composites, including those with conducting polymers for supercapacitors. The reactors in the process are industrially adoptable, promising a great technological and commercial future.